E-Government in Ghana: the benefits and challenges - Abusamhadana, Ghassan A. O.; Bakon, Kinn Abass; Nur Fazidah Elias, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The result of substantial investment and the formulation of impressive policies for e-government implementations has transitioned Ghana from a mediocre to a high e-government readiness in the latest United Nations Biannual E-Government Development Index (EGDI). Ghana is the only African country to achieve this feat. However, how e-government service delivers benefits to Ghanaians and the challenges this technology is encountering seems to be overlooked by researchers in extant academic discourses. As a result, important scientific knowledge about this topic in the context of Ghana is missing. This paper aims to review articles on e-government to identify its merits to the Ghanaian public and businesses and single out the challenges it faces. The narrative review method was employed to search, review, and synthesise the extant literature. The review showed that there is a paucity of e-government related literature in the context of Ghana. Among the few articles that were found and reviewed, the benefits associated with e-government are; (1) reduction of corruption prospects, (2) efficiency of government services delivery, (3) access to government services, and (4) cost reduction. Moreover, the challenges associated with e-government are; (1) digital divide and its four dimensions, (2) culture challenge, (3) sabotaging of government infrastructure, (4) power interruptions, (5) citizens trust issues, (6) security threats, and (7) low public knowledge. This article contributes to the limited body of research on e-government in developing countries, particularly Ghana, by mapping a potential field of research, synthesising the current knowledge of e-government in Ghana, and creating an agenda for further research. Also, the up-to-date knowledge provided by this paper could assist the authorities in making prudent e-government policies.